Difference of SARS-CoV-2 infection and influence factors between people with and without HIV infection - Jianhui Yang; Esben Strodl; Dandan Zhang; Haibo Jiang; Kun Chu; Shiwen Tan; Zehao Ye; Hongbo Shi; Feng Tong; Weiqing Chen (BMC Public Health)
Abstract Background There are mixed findings in the literature regarding the association between HIV status and the risk of COVID-19 infection. Thus, we aimed to estimate the association between characteristics of HIV infection and the risk of COVID-19 Infection in a Chinese sample. Methods We conducted a cross-sectional survey of 1995 people living with HIV (PLWH) and 3503 HIV-negative adults in Ningbo, China. We compared the prevalence rates of the SARS-CoV-2 infection and the long nucleic acid conversion time (more than 2 weeks) among PLWH and HIV-negative participants, respectively. In addition, we explored the risk factors associated with SARS-CoV-2 infection and the long nucleic acid conversion time among the two groups. Results Overall, 1485/1995 (74.4%) PLWH and 2864/3503 (81.8%) HIV-negative people were infected with SARS-CoV-2. Among the SARS-CoV-2-infected participants, 437/1485 (29.4%) PLWH and 649/2864 (22.7%) HIV-negative people had the long nucleic acid conversion time. After controlling for the potential confounders, the rate of the SARS-CoV-2 infection was lower among the PLWH than the HIV-negative group (adjusted OR = 0.836, 95% CI = 0.706–0.990). However, PLWH had a significantly higher risk of the long nucleic acid conversion time after the SARS-CoV-2 infection (adjusted OR = 1.417, 95% CI = 1.176–1.707) than the HIV negative participants. Compared with those who did not receive ART, PLWH adults who received ART significantly had the increased risk of SARS-CoV-2 infection. Furthermore, HIV-negative participants receiving COVID-19 vaccines significantly displayed the decreased likelihood of the long nucleic acid conversion time after the SARS-CoV-2 infection. Conclusions Our study indicates that different HIV Infection status was significantly and differently associated with the SARS-CoV-2 infection and the long nucleic acid conversion time. However, the further studies are needed to confirm the effect of ART and COVID-19 vaccines on SARS-CoV-2 infection in PLWH.